Results of traumatic injuries of milk teeth and the alveolar process – case study - Rahnama, Mansur; Szczerba-Gwóźdź, Joanna; Orzędała-Koszel, Urszula (Journal of Stomatology, 2015)
Injuries to the teeth and nearby tissues are the most frequent cause of children’s presentation at the dental surgery. Complications after injury to milk teeth, the alveolar process of the maxilla and the alveolar part of the mandible are frequently diagnosed in distant time from the trauma occurring. This study describes the case of a female patient aged 2.5 years who experienced injury to the upper lip, the alveolar process of the maxilla and teeth 51 and 52 as a result of a fall. At the age of 12, during radiographic examination, the same patient was diagnosed with a pathological lesion in the vicinity of tooth 12, which, after surgical removal in one piece, was identified in the histopathological examination as odontoma complexum.